Positive definite kernels on the set of integers, stability, some properties and applications - DE LA BARRERA , Arnaldo; FERRER, Osmin; SANABRIA, Jos´e (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We define and investigate a class of positive definite kernel so called equivalent-kernel. We formulate and prove an analogous of Paley-Wiener theorem in the context of positive definite kernel. The main ingredient in the proof is Kolmogorov decomposition. Finally, some applications to stochastic processes are given. Mathematics Subject Classification (2010): 42A82, 60G10. Received 14 February 2020; Accepted 13 April 2020.